Export Platform FDI as a Concept for Growth - Selected Global Experiences - Mariusz Omelańczuk (Entrepreneurial Business and Economics Review, 2013)
Objective: The main idea presented in the paper is based on the research devoted to interrelations between foreign direct investments (FDI) and export activities that result in the development of the specific form of foreign direct investment – Export Platform (EPFDI).